5.25. Rozwiąż dany układ równań metodą podstawiania. (x – 3)/2 – (2x + y)/4 = (x – y)/8 (2(x – y))/7 – (x – 3y)/21 = y/3 a) x+2y 2 – x-y 8 = 3y+1 4 2x+2y =7 b) ( (1 – 2x)/3 – (5 – 3y)/3 = 0 big)=y+x+2 3x x/4 – 7/4 = – 1, \qquad (5x)/3 + (3y)/3 = 16 2 8 \ 2x-3y 3 – x+3y 6 =x-4y 3x – 4y =11 (4y – 3x)/18 – (y + 4)/6 = y/9, \qquad (y – x)/2 = 8y + 4x

 5.25. Rozwiąż dany układ równań metodą podstawiania. (x – 3)/2 – (2x + y)/4 = (x – y)/8 (2(x – y))/7 – (x – 3y)/21 = y/3 a) x+2y 2 – x-y 8 = 3y+1 4 2x+2y =7 b) ( (1 – 2x)/3 – (5 – 3y)/3 = 0 big)=y+x+2 3x x/4 – 7/4 = – 1, \qquad (5x)/3 + (3y)/3 = 16 2 8 \ 2x-3y 3 – x+3y 6 =x-4y 3x – 4y =11 (4y – 3x)/18 – (y + 4)/6 = y/9, \qquad (y – x)/2 = 8y + 4x